Exploring the implementation of STEM education through mathematical modelling activities in schools - Aslipah Tasarib; Roslinda Rosli; Azmin Sham Rambely (LUMAT)
For the last few decades, mathematical modelling has been an important topic in school education. Practical approaches to applying mathematical concepts to real-world scenarios are beneficial to students. The process of seeking solutions to real-world problems could foster students’ inquiry skills and have more impactful advantages. However, the implementation of mathematical modelling in schools presents numerous challenges in terms of finding its practical application. Integrating modelling activities with STEM education benefits students by providing practical applications. This research sought to investigate the growth and development of research activities in the area of the integration of STEM education into mathematical modelling by using a bibliometric approach. We followed the PRISMA guidelines and conducted a thorough search in the Scopus database to find important articles published between 2005 and 2025, looking at the article titles, abstracts, and keywords. We conducted an analysis of 139 relevant articles to investigate the implementation of mathematical modelling in the context of integrated STEM education. We analyzed the data using VOSviewer, which performs co-occurrence analyses of authors and keywords. We used Harzing's Publish or Perish software for citation metrics and analysis and Microsoft Excel for frequency analysis. The results indicate that the United States happened to be the most productive country in this field, with 53.24% of the publications. The most productive authors and institutions also show that more than half of the top ten publications in this area were from the United States. The findings of this study will enhance the understanding of integrating STEM education and mathematical modelling in school. It also demonstrates that the scope of this research is relevant, potentially improving the quality of teaching and learning and supporting future studies in the mathematics education field.